2020
DOI: 10.22541/au.160391883.33604347/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Frailty on Epistaxis admission, a retrospective cohort study

Abstract: This a preprint and has not been peer reviewed. Data may be preliminary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In light of these facts, a potential bias in our results should not be overlooked – possibly many DOAC patients were treated in an out‐patient manner and are omitted from this review. Six 7,8,20,21,23,24 from eight included studies reported on in‐ and out‐patients, and here, no significant difference concerning admission rate in the meta‐analysis has been noted ( p = .12, Table 4). Nevertheless, it seems that a plethora of out‐patient data remains unprocessed.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In light of these facts, a potential bias in our results should not be overlooked – possibly many DOAC patients were treated in an out‐patient manner and are omitted from this review. Six 7,8,20,21,23,24 from eight included studies reported on in‐ and out‐patients, and here, no significant difference concerning admission rate in the meta‐analysis has been noted ( p = .12, Table 4). Nevertheless, it seems that a plethora of out‐patient data remains unprocessed.…”
Section: Discussionmentioning
confidence: 63%
“…With regards to the rate of admission to hospital as a percentage of all patients seen in the emergency room, data were extracted from six studies 7,8,20,21,23,24 . No statistical significance between the groups could be found (OR = 0.76, 95% CI 0.54 to 1.07, p = .12; Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the rate of admission to hospital as a percentage of all patients seen in the emergency room, data was extracted from 6 studies 7,8,20,21,23,24 . No statistical significance between the groups could be found (OR= .76, 95% CI .54 to 1.07, P= .12; Table 4).…”
Section: Admission Rate Meta-analysismentioning
confidence: 99%